Power transmission and interoperability of different coils in wireless charging of electric vehicles - Zhao, Zekai (Nanyang Technological University, 2023)
The surging demand for electric vehicles (EVs) has spurred the development of new charging methods that are more convenient, efficient, and safe. Wireless power transfer (WPT) technology offers a promising alternative to traditional plug-in systems, as it enables EVs to be charged without the need for cables. However, the efficiency and performance of WPT systems depend on the type of coupled coils used, which can vary widely among different manufacturers. This raises concerns about interoperability and standardization.